Bacteria-laden microgels as autonomous three-dimensional environments for stem cell engineering. (March 2019) - Witte, K.; Rodrigo-Navarro, A.; Salmeron-Sanchez, M.
Abstract: A one-step microfluidic system is developed in this study which enables the encapsulation of stem cells and genetically engineered non-pathogenic bacteria into a so-called three-dimensional (3D) pearl lace–like microgel of alginate with high level of monodispersity and cell viability. The alginate-based microgel constitutes living materials that control stem cell differentiation in either an autonomous or heteronomous manner. The bacteria ( Lactococcus lactis ) encapsulated within the construct surface display adhesion fragments (III7-10 fragment of human fibronectin) for integrin binding while secreting growth factors (recombinant human bone morphogenetic protein-2) to induce osteogenic differentiation of human bone marrow–derived mesenchymal stem cells. We concentrate on interlinked pearl lace microgels that enabled us to prototype a low-cost 3D bioprinting platform with highly tunable properties.